2016
DOI: 10.1007/s10886-016-0752-5
|View full text |Cite
|
Sign up to set email alerts
|

Do Fruit Ripening Volatiles Enable Resource Specialism in Polyphagous Fruit Flies?

Abstract: Frugivorous tephritid fruit flies have lineages with high levels of host generalism. These insects use olfaction to locate fruits, but how they are able to recognize the odors of so many different host species is poorly understood. We used a series of behavioral experiments to investigate the role of fruit ripening volatiles as host cues in the Queensland fruit fly, Bactrocera tryoni (Froggatt), a polyphagous pest in Australia. Odors of mature guava (Psidium guajava) attracted female and male flies more strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 55 publications
4
50
0
Order By: Relevance
“…Some of these compounds have been reported previously in fruits. For example, ethyl propanoate, which has a pineapple-like odor 51 , is a common volatile in many ripe fruits that attract B. tryoni females including mango and apple 52 . Ethyl propanoate has also been considered as an attractant for other frugivorous pest insects.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these compounds have been reported previously in fruits. For example, ethyl propanoate, which has a pineapple-like odor 51 , is a common volatile in many ripe fruits that attract B. tryoni females including mango and apple 52 . Ethyl propanoate has also been considered as an attractant for other frugivorous pest insects.…”
Section: Discussionmentioning
confidence: 99%
“…Jayanthi et al 2012Jayanthi et al , 2014a, fly species (e.g. B. tryoni, Cunningham et al 2016) and environmental cues (e.g. food and host plant odours, contextual odours), and pay particular attention to volatiles whose detection may have fallen below noise levels due to positional effects or low abundance of corresponding sensory neurons (Olsson & Hansson 2013;Biasazin et al 2014, Jacob et al 2017.…”
Section: Esters Are Overrepresentedmentioning
confidence: 99%
“…In contrast, our knowledge of tephritid olfaction is rather fragmentary (Fombong et al 2016), in spite of their global economic significance. In semi-field trials, Cunningham et al (2016) found a combination of only three short-chain aliphatic esters derived from guava that was attractive to the Queensland fruit fly, Bactrocera tryoni (Froggatt). While this does provide a horizon for using synthetic blends for monitoring or control of tephritids, the use of three highly related compounds leaves the vast majority of volatiles and their cognate olfactory channels 'untapped' (Siderhurst & Jang 2006Jayanthi et al 2012;Biasazin et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the last 50 years, substantial efforts have been invested into identifying visual and olfactory attractants to implement in “lure and kill” strategies as part of sustainable pest management programs. While B. tryoni females are attracted to a three-component mixture of fruit derived esters ( Cunningham et al, 2016 ), no effective lures have been developed so far. Male flies, on the other hand, are strongly attracted to the phytochemical compound raspberry ketone and its synthetic analog called “cuelure”.…”
Section: Introductionmentioning
confidence: 99%